Optimization of Law No. 6/2014 on Villages as a Prevention of Village Fund Corruption in Sempajaya Village - Jefri, Jefri; Wahyu Marpaung, Linda (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Law No. 6/2014 on Villages gives villages broad authority in managing governance and development. The increase in village fund allocations from IDR 20.7 trillion in 2015 to IDR 71 trillion in 2024 places villages at the center of national development. However, along with this, there has been an increase in cases of corruption of village funds, as reported by ICW. Factors causing corruption include unclear regulations, personal factors of the village head, and lack of community participation. Transparency and accountability in the management of village funds are key in preventing corruption. Therefore, optimizing the implementation of the Village Law is necessary to ensure that village funds are used as intended and to avoid legal problems. This research uses an empirical juridical method with a focus on analyzing primary and secondary data, collected through interviews. The approaches include statutory, conceptual, and case, with qualitative data analysis to understand and present the findings. Sempajaya Village has successfully implemented Law No. 6/2014 on Villages by applying transparency and accountability in the management of village funds. Active community participation in the planning, implementation, and monitoring of village funds creates an open and accountable government. This ensures that village funds are used for development, empowerment, and community services, preventing corruption, and realizing independent, strong, and prosperous villages.